Microglia Response During Parkinson’s Disease: Alpha-Synuclein Intervention - Ferreira, Sara A.; Romero-Ramos, Marina (Frontiers in Cellular Neuroscience, 2018)
TThe discovery of the central role played by the protein alpha-synuclein in Parkinson’s disease and other Lewy body brain disorders has had a great relevance in the understanding of the degenerative process occurring in these diseases. In addition, during the last two decades, the evidence suggesting an immune response in Parkinson’s disease patients have multiplied. The role of the immune system in the disease is supported by data from genetic studies and patients, as well as from laboratory animal models and cell cultures. In the immune response, the microglia, the immune cell of the brain, will have a determinant role. Interestingly, alpha-synuclein is suggested to have a central function not only in the neuronal events occurring in Parkinson’s disease, but also in the immune response during the disease. Numerous studies have shown that alpha-synuclein can act directly on immune cells, such as microglia in brain, initiating a sterile response that will have consequences for the neuronal health and that could also translate in a peripheral immune response. In parallel, microglia should also act clearing alpha-synuclein thus avoiding an overabundance of the protein, which is crucial to the disease progression. Therefore, the microglia response in each moment will have significant consequences for the neuronal fate. Here we will review the literature addressing the microglia response in Parkinson’s disease with an especial focus on the protein alpha-synuclein. We will also reflect upon the limitations of the studies carried so far and in the therapeutic possibilities opened based on these recent findings.